2023
DOI: 10.3233/wor-220607
|View full text |Cite
|
Sign up to set email alerts
|

Workplace mobbing, group cohesion and intraindividual variables in nurses from a rural hospital in Northern Greece: A correlation study

Athanasios Varytis,
Vaitsa Giannouli

Abstract: BACKGROUND: High levels of mobbing are reported in Greek nurses, but the intraindividual and perceived group emotional correlates are little investigated. OBJECTIVE: To determine the relationship between workplace mobbing (specifically in the nursing sector of a public rural hospital in Greece) and emotional correlates. METHODS: Questionnaires measuring emotional aspects such as Negative Act Questionnaire – Revised (NAQ-R) for measuring perceived exposure to bullying and victimization at work, Maslach Burnout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As for now, shift work has been reported to increase the risk of cardiovascular diseases [5,8,9], metabolic diseases [3,10], cancer [11,12], cognitive disorders [13][14][15][16], mortality, and so on. Shift workers' workplaces, relationships with coworkers, and individual characteristics are all factors that may influence their health conditions [17]. Some studies have found that shift work increases the risk of anxiety and depression [13,18], whereas others suggest that shift workers have better psychiatric well-being and mental health than non-shift workers [19].…”
Section: Introductionmentioning
confidence: 99%
“…As for now, shift work has been reported to increase the risk of cardiovascular diseases [5,8,9], metabolic diseases [3,10], cancer [11,12], cognitive disorders [13][14][15][16], mortality, and so on. Shift workers' workplaces, relationships with coworkers, and individual characteristics are all factors that may influence their health conditions [17]. Some studies have found that shift work increases the risk of anxiety and depression [13,18], whereas others suggest that shift workers have better psychiatric well-being and mental health than non-shift workers [19].…”
Section: Introductionmentioning
confidence: 99%